Therapeutic effects of extended daily hemofiltration and intermittent hemodialysis for systemic inflammatory response syndrome with acute kidney injury - FENG Xue-fang; ZHOU Rong; XU Ya-hong; ZHANG Yun; CHEN Ming-dong; SHEN Jie (Linchuang shenzangbing zazhi)
Objective To compare the effect of extended daily hemofiltration(EDHF) and intermittent hemodialysis(IHD) for patients with systemic inflammatory response syndrome(SIRS) and acute kidney injury(AKI).Methods Forty patients with SIRS and AKI in Yangpu Hospital from Jan.2010 to May 2013 were collected prospectively.Patients were given EDHF or IHD in addition to the routine management The following endpoints were measured and compared between two groups:the baseline level,the progression of disease(including mortality rate in hospital,kidney survival rate,length and expenses of hospitalization,and the incidence of disease complications),the serum BUN and creatinine levels.Results(1) 17(85%) patients in the EDHF group got through the acute phase of disease and 3(15%) patients did not survive,while in the IHD group 15(75%) patients survived and 5(25%) patients died.No significant difference in survival rate was found between the two groups.Fourteen patients(70%) in the EDHF group got rid of dialysis,while in the IHD group,9out of 20(45%) did There was also no significant difference in kidney survival rate between the two groups.The average days of hospitalization in the EDHF group was(32.6 ± 8.6) days,significantly shorter than in the IHD group(39.2 ± 11.5) days(P<0.05),but the expenses of hospitalization was comparable between two groups(P>0.05).(2) The creatinine level on the 5th day after hemodialysis in the EDHF group was(243.5±92.8) μmol/L,significantly lower than that in the IHD group(363.8 ± 209.0) μmol/L(P<0.05).Conclusions In management of SIRS with AKI,it seemed that the EDHF lowered the mortality rate in hospital and improved the kidney survival rate more efficiently than IHD did,although only the trend but not statistical significance was observed.